Identity Construction of the Main Character in the Novel “Mashatun” by Hani As-Salmi: An Analysis of Gramsci's Hegemony Theory - Khusniyah, Farikhatul; Arief Rahman Hakim (Universitas Cokroaminoto Palopo, 2025)
This research aims to determine how the forms of Israeli power hegemony psychologically impact the Palestinian people, as represented through the main character in Hani As-Salmi's novel